The heart and Fabry-Anderson’s disease - Reis Pina, Paulo (2003)
Fabry-Anderson’s disease is a progressive X-linked recessive disorder. It is included in the group of at least 41 unique genetic lysosomal storage diseases.It is caused by a deficiency of alpha-galactosidase A, which leads to an accumulation of neutral glycosphingolipids in most visceral tissues and fluids of the body which results in several clinical manifestations.Fabry-Anderson’s disease is characterized by acroparaesthesias, cutaneous angiokeratomas, hypohidrosis, corneal opacities, and cardiovascular, gastrointestinal, and central nervous systems disturbances. Deposition of neutral glycosphingolipids in cardiac cells implies varied disturbances, with several symptoms, depending on patient’s sex and age.Some individuals develop a cardiac variant of Fabry-Anderson’s disease. About 3 to 6% of asymptomatic men, with left ventricular hypertrophy, have the variant condition. Left ventricular hypertrophy can be used as a marker of disease severity. It is thought that 4 to 8% of patients with hypertrophic non-obstructive cardiomyopathy, considered as idiopathic, have Fabry-Anderson’s disease. This disease ought to be considered and investigated (through biochemical study or an endomyocardial-biopsy specimen) as a possible cause of a cardiomyopathy.Fabry-Anderson’s disease has a high morbidity and death occurs in early adulthood, by the fourth or fifth decades of life, due to vascular disease of the kidney, heart or brain.